Prosperity Through Rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
'Prosperity Through Rice' is a Joint programme being run by the International Rice Research Institute (IRRI) and the University of the Philippines, with financial backing from the Asian Development Bank. Its aim is to investigate ways of using the...